2020 IEEE 21st International Symposium on "A World of Wireless, Mobile and Multimedia Networks" (WoWMoM) 2020
DOI: 10.1109/wowmom49955.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Short: Achieving Energy Efficiency in Dense LoRaWANs through TDMA

Abstract: Long Range Wide Area Networks (LoRaWANs) have recently emerged as a hot research topic for their capability to collect sporadic data from a great number of widely spread low power devices. By enabling low-cost low-traffic wireless communications at large scale, such networks can be adopted in many application domains, including smart agriculture, logistics, and emergency detection among others. LoRaWAN employs a pure ALOHA default medium access scheme, that limits the maximum achievable throughput to 18%. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Several works in the literature have proposed channel access improvements to increase the scaling capabilities of LoRa, many of them based on synchronization and the consequent possibility to slice time into slots. Such enhancement allows to increase the maximum throughput, but we showed in a previous contribution [4] that the additional energy consumption induced by the process only makes it beneficial for high traffic situations.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Several works in the literature have proposed channel access improvements to increase the scaling capabilities of LoRa, many of them based on synchronization and the consequent possibility to slice time into slots. Such enhancement allows to increase the maximum throughput, but we showed in a previous contribution [4] that the additional energy consumption induced by the process only makes it beneficial for high traffic situations.…”
Section: Introductionmentioning
confidence: 91%
“…The figure shows that for this deployment, Class A is capable of offering a maximum of 220 B • s −1 , while the scheduled access peaks at 440 B • s −1 . It therefore provides a 100% capacity increase, which is better than the 88% increase offered by slotted ALOHA over Class S in [4].…”
Section: A Preliminary Deployment Fingerprintingmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been found that introduction of LBT has both positive (e.g., the improved delivery rate for dense network and the potential for increasing the throughput, especially relevant for downlink) and negative consequences (e.g., the increased energy consumption and potentially lower performance in the multigateway environment). The use of slotted ALOHA and schedule-based (i.e., time-division multiple access (TDMA)) protocols have also been suggested [ 51 , 54 , 55 , 56 ]. The latter ones have been found especially beneficial for industrial use cases requiring guaranteed latency and higher reliability [ 55 , 56 ].…”
Section: Lorawan Technology At a Glancementioning
confidence: 99%